The role of stress‐regulation genes in moderating the association of stress and daily‐life psychotic experiences. (2nd September 2017) - Cristóbal‐Narváez, P.; Sheinbaum, T.; Myin‐Germeys, I.; Kwapil, T. R.; de Castro‐Catala, M.; Domínguez‐Martínez, T.; Racioppi, A.; Monsonet, M.; Hinojosa‐Marqués, L.; van Winkel, R.; Rosa, A.; Barrantes‐Vidal, N.
Abstract : Objective: The interaction of single nucleotide polymorphisms with both distal and proximal environmental factors across the extended psychosis phenotype is understudied. This study examined (i) the interaction of relevant SNPs with both early‐life adversity and proximal (momentary) stress on psychotic experiences (PEs) in an extended psychosis sample; and (ii) differences between early‐psychosis and non‐clinical groups for these interactions. Methods: Two hundred and forty‐two non‐clinical and 96 early‐psychosis participants were prompted randomly eight times daily for 1 week to complete assessments of current experiences, including PEs and stress. Participants also reported on childhood trauma and were genotyped for 10 SNPs on COMT, RGS4, BDNF, FKBP5, and OXTR genes. Results: Unlike genetic variants, distal and proximal stressors were associated with PEs in both samples and were more strongly associated with PEs in the early‐psychosis than in the non‐clinical group. The RGS4 TA and FKBP5 CATT haplotypes interacted with distal stress, whereas the A allele of OXTR (rs2254298) interacted with proximal stress, increasing momentary levels of PEs in the early‐psychosis group. No interactions emerged with COMT or BDNF variants. Conclusion: Individual differences in relevant stress‐regulation systems interact with both distal and proximal psychosocial stressors in shaping the daily‐life manifestation of PEs across the psychosis continuum.